1988
DOI: 10.1002/mrm.1910080213
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo13C NMR Spectroscopy of the Human Prostate

Abstract: The metabolism of the normal and hyperplastic human and rat prostate differs from that of other tissues in that this organ supports and secretes high concentrations of citrate. During the dedifferentiation process that is characteristic of neoplasia, the ability of the prostate to maintain these high citrate levels is markedly diminished. We undertook a natural abundance 13C NMR study of the human and rat prostate in vitro and the human organ in vivo in order to determine whether the amounts of citrate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Our long history of applications of NMR to prostate cancer diagnosis 2,25,26,[33][34][35][36][37] suggested that we turn to this area for a candidate cell-surface epitope to discriminate between cancer cells and normal, non-malignant cells. Research on prostate cancer-specific cell markers 25,[27][28][29] led to the identification of PSMA, the folate receptor, as a cell-surface protein that is highly-overexpressed on prostate tumors.…”
Section: Specific Binding Of Anti-psma-conjugated Spions To Psma-posimentioning
confidence: 99%
“…Our long history of applications of NMR to prostate cancer diagnosis 2,25,26,[33][34][35][36][37] suggested that we turn to this area for a candidate cell-surface epitope to discriminate between cancer cells and normal, non-malignant cells. Research on prostate cancer-specific cell markers 25,[27][28][29] led to the identification of PSMA, the folate receptor, as a cell-surface protein that is highly-overexpressed on prostate tumors.…”
Section: Specific Binding Of Anti-psma-conjugated Spions To Psma-posimentioning
confidence: 99%
“…Several review studies have examined the differences in metabolite levels between malignant and normal tissues in both animal (6)(7)(8) and human cancers (9,10). Examples of metabolites that have potential diagnostic significance include citrate in prostate tumors (11,12), glycogen in kidney tumors (12), N-acetyl aspartate in brain tumors (13), and lactate and phospholipid metabolites in prostrate, colon, and lung (12,14). The ability of NMR spectroscopy to detect metabolite profiles indicative of tumor differentiation is important because in many tumor types, particularly liposarcoma, the histologic type is one of the most important factors in predicting risk for relapse and overall survival.…”
mentioning
confidence: 98%
“…In the first study, proton-coupled natural-abundance 13 C NMR spectra were acquired from a 4 · 4 · 4 cm region of normal human prostate using a depth-resolved surface-coil spectroscopy sequence and a dual-tuned, concentric 1 H/ 13 C 20-cm-diameter transmit and 7.5-cm-diameter receive surface coils in a clinical 1.5-T MRI scanner (8). It was concluded that although citrate could be detected in the natural-abundance 13 C NMR spectra of the normal human prostate, more sensitive techniques involving proton decoupling and the use of 13 Clabeled citrate precursors may be necessary to attain clinically relevant data (9). In the second study, proton-enhanced 13 C imaging or spectroscopy was performed on phantoms and ex vivo human prostate specimens using polarization transfer techniques in which the sensitivity of the carbon signal was enhanced by transferring the proton spin order to the attached carbon (10).…”
mentioning
confidence: 99%